4-Chloro-N-[(E)-(3,4-dimethoxyphenyl)methylidene]aniline - M. Nawaz Tahir; Muhammad Ilyas Tariq; Muhammad Sarfraz; Shahbaz Ahmad; Riaz H. Tariq (Acta Crystallographica Section E, 2010)
The asymmetric unit of the title compound, C15H14ClNO2, contains two molecules with significantly different conformations: the dihedral angles between the 4-chloroaniline and 3,4-dimethoxyphenyl (excluding C atoms) moieties are 19.68 (7) and 45.54 (4)°. In the crystal, the molecules are linked by C—H...O hydrogen bonds and weak C—H...π interactions.